Immune mechanisms of protection: can adjuvants rise to the challenge? - McKee, Amy S (BioMed Central, 2010)
For many diseases vaccines are lacking or only partly effective. Research on protective immunity and adjuvants that generate vigorous immune responses may help generate effective vaccines against such pathogens.